Yours Truly - Frederick, Heather Vogel (Frederick, Heather Vogel. Pumpkin Falls mystery., 2017)
When someone tries to sabotage the maple trees on her friend Franklin's family farm, Truly Lovejoy rallies the Pumpkin Falls Private Eyes to investigate.